A Maximal Incremental Test in Cyclists Causes Greater Peripheral Fatigue in Biceps Femoris. Issue 3 (2nd July 2020) - García-García, Oscar; Cuba-Dorado, Alba; Riveiro-Bozada, Alicia; Carballo-López, Javier; Álvarez-Yates, Tania; López-Chicharro, José
ABSTRACT: Purpose : The aim of this study was to determine the changes in neuromuscular contractile properties in elite cyclists associated to the peripheral fatigue produced in a maximal incremental test in cycle ergometer. Methods : Forty-eight volunteers' well-trained male cyclists were evaluated during the competition season within a recovery microcycle. Tensiomyography was used before and after performing an incremental test until exhaustion in cycle ergometer to measure the radial muscle belly displacement of the vastus lateralis (VL), rectus femoris (RF), and biceps femoris (BF) on the dominant leg. Maximum radial muscle belly displacement (Dm), contraction time (Tc), delay time (Td), sustain time (Ts), and radial displacement velocity (Vrd) were measured. Mixed-design factorial analysis of variance was used to detect changes in the mechanical and neuromuscular characteristics after a maximal incremental exercise test. Results : The results show in the evaluated muscles a moderate-large decrease ( p < .01, η2 = 0.06–0.51) in Tc, Td, Dm, Ts, and Vrd. This decrease occurs more sharply in the BF than in RF or VL. Conclusion : An incremental effort until exhaustion produces peripheral fatigue associated with a decrease in Dm, Tc, Td, Ts, and Vrd, being more pronounced in biceps femoris than in vastus lateralis and rectus femoris. Coaches can use these changes found in the contractile properties as a reference to detect the muscle fatigue degree that certain training models pose for the cyclist.